Pengaruh Kualitas Pelayanan Dan Kinerja Petugas Terhadap Tingkat Kepuasan Masyarakat Dalam Pelaksanaan Program Layanan Kelurahan Kecamatan Online (LAKON) Kecamatan Padang Panjang Barat Dengan Fasilitas Sebagai Variabel Intervening - Arosa Apriyani; Yulihasri Yulihasri (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
The Influence of Service Quality and Officer Performance on the Level of Community Satisfaction in the Implementation of Online District Village Service Program (LAKON) Padang Panjang Barat District With Facilities As Intervening Variables. The total population in this study was 1,073 people while the sample was 130 people. With using the age of Hair et al, Data was collected by distributing questionnaires with a Likert scale model and then being tested for the validity and reliability of the questionnaire. The data analysis technique used is the Smart PLS method. The purpose of this study is to see the relationship between the effect of the independent variables on the dependent variable. The results of this study are a). service quality has a positive and significant influence on community satisfaction in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District b). The performance of officers has a positive and significant influence on community satisfaction in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District. c). service quality has a positive and significant influence on the facilities in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District. d). the performance of officers has a positive and significant influence on the facilities in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District. e). The facility has a positive and significant influence on community satisfaction in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District. f). service quality cannot be mediated by facilities on community satisfaction in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District. g). the performance of officers cannot be mediated by facilities on community satisfaction in the Implementation of the Online District Village Service Program (LAKON) in Padang Panjang Barat District Keywords: Service Quality (X1) Officer Performance (X2) Facilities (M) and Community Satisfaction (Y).